Early warning indicators of asset price boom/bust cycles in emerging markets - Alexey Ponomarenko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2012)
We apply recently developed early warning indicators systems to a cross-section of emerging markets. We find that, with little or no modification, models designed to predict asset price booms/busts in advanced countries may be useful for emerging markets. The concept of monitoring a set of asset prices, real activity (especially investment) and financial (especially credit) indicators is generally found to be efficacious.
URN:NBN:fi:bof-201408072001
Keywords: E37; E44; E51; 330; early warning indicators; asset prices; emerging markets